Health‐related quality of life amongst primary caregivers of children with intellectual disability. Issue 2 (15th December 2019) - Arora, S.; Goodall, S.; Viney, R.; Einfeld, S.; ,
Abstract: Background: Children with intellectual disability (ID) frequently have significant educational, social and health care needs, resulting in caregivers often experiencing a wide range of negative effects. This paper aims to determine the impact of childhood ID on caregivers' health‐related quality of life (HRQoL) across co‐morbid diagnostic groups. The second aim of this study is to determine the risk factors associated with lower HRQoL in this population. Methods: Caregivers of a child with ID aged between 2 and 12 years old completed an online survey to determine their HRQoL using the EQ‐5D‐5L measure. They were also asked demographic questions and about their dependent child's level of behavioural and emotional difficulties. Results: Of the total sample of 634 caregivers, 604 caregivers completed all five questions of the EQ‐5D‐5L. The mean age of caregivers was 39.1 years and 91% were women. Caregivers spent on average 66.6 h per week caring for their child related to their child's disability. The mean EQ‐5D‐5L score of caregivers was 0.80 (95% confidence interval: 0.79, 0.82), which is below the estimated Australian population norms (mean utility score of 0.92) for the age‐equivalent population. Caregivers of children with autism spectrum disorders reported the lowest HRQoL (0.77, 95% confidence interval: 0.74, 0.79) of the five included co‐morbid diagnostic groups. Caregivers with a lower income, a perceived low level of social support and children with higher degree of behavioural and emotional problems were likely to have a statistically lower HRQoL. Conclusions: This is the first study to produce utility values for caregivers of children with ID. The utility values can be used to compare health states and can be used to inform comparative cost‐effectiveness analyses. Demonstrating that caregivers of children with ID have reduced HRQoL and that this is associated with the degree of behavioural and emotional problems has important policy implications, highlighting the potential for policy interventions that target behavioural and emotional problems to improve outcomes for caregivers.